Efikasi Chitosan untuk Memperpanjang Flower Longevity Bunga Anggrek Dendrobium Hibrida dalam Pot (Potted Flower) - I MADE SUKEWIJAYA (Agrotrop : Journal on Agriculture Science, 2013)
Effication of Chitosan on Lengthening The Flower Longevity of Potted Orchid ofDendrobium Hybrid. The aim of the current research is to investigate general effects of Chitosantreatment on the flowering of Dendrobium orchid and to find out the optimum concentration of Chitosanin lengthening flower longevity of potted orchid of Dendrobium hybrid. Results of the research showedthat Chitosan application significantly affected variables of the number of flower per-plant, the length ofindividual flower, period of time to get full blooming, and the flower longevity. The best results for thoseof variables was achieved with Chitosan concentration of 0.15%.